Analysis of Extreme Precipitation Events in the Mountainous Region of Rio de Janeiro, Brazil - Lopez, Maria del Carmen Sanz; Pinaya, Jorge Luiz Diaz; Pereira Filho, Augusto José; Vemado, Fe-Lipe; Reis, Fábio Augusto Gomes Vieira [UNESP] (MDPI, 2023)
Extreme rainfall events cause diverse loss of life and economic losses. These disasters include flooding, landslides, and erosion. For these intense rainfall events, one can statistically estimate the time when a given rainfall volume will occur. Initially, this work estimated rainfall volumes for the mountainous region of Rio de Janeiro, and the frequency with which rainfall events occur. For this, we analyzed daily precipitation data using the ANOBES method and the Gumbel statistical distribution to estimate return times. Extreme prec’ipitation volumes of up to 240 mm per day were identified in some locations, with 100 years or more return periods. On 11 January 2011 precipitation volumes were high, but on 12 January they were extreme, similar to the 100-year return time data. The analysis method presented enables the determination of the return time of heavy rainfall, assisting in the prevention of its effects. Knowledge of the atmospheric configuration enables decision support. The atmospheric systems that combined to cause the event were local circulations (orographic and sea breeze) and large-scale systems (SACZ and frontal systems).
Keywords: extreme precipitation events; floods; landslides; rainfall